Tinjauan Literatur: Peranan Blue Economy dalam Meningkatkan Pendapatan Masyarakat Pesisir Melalui Sumber Daya Perikanan di Sumatera Utara - Ardhi Sahjaya; Rifaldy Yusliandi; Lian Diza Loriva Siregar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This article discusses the role of the Blue Economy in increasing the income of coastal communities in North Sumatra through the utilization of fisheries resources. With great marine potential, including fishing that reaches more than 1 million tons per year, the North Sumatra region faces several challenges such as, low quality of human resources and limited access to technology. The Blue Economy offers a sustainable approach to managing marine resources, which not only promotes economic growth and community welfare, but also maintains the health of marine ecosystems. Through a qualitative method, we selected sources of articles found in databases in journals spread across various indexes and other sources. The research process began with literature mapping related to the role of the Blue Economy in increasing the income of coastal communities through optimizing fisheries resources, published in the last five years (2020-2024). Furthermore, group discussions were held to deepen the content analysis of the selected literature. The main objective of this research was to provide comprehensive information from the literature related to Blue Economy studies in economics and development. It was found that overall, the Blue Economy in North Sumatra has a significant positive impact on coastal communities. By managing fisheries resources and the environment more sustainably, opening up new opportunities through tourism, and improving the quality of fisheries products, the Blue Economy creates more equitable welfare, preserves nature, and supports the income of coastal communities in the long term.